Why Did People Argue on Twitter? Scrutinizing Argumentation Strategies Used in the Tweets of #InternationalWomensDay - Isnaini, Nur Alfiana (Universitas Sebelas Maret, 2023)
The phenomenon reflected in the tweets used in #InternationalWomensDay as the campaign has provided many people to argue freely on social media platform. Giving an argumentation will conceal the hidden problems spread in the society. Several public problems will be left without any attention. Therefore, this study aims to scrutinize argumentation strategies used by Twitter users in tweets using the #InternationalWomensDay using the Critical Discourse Analysis approach. This present research employs argumentation strategies theory proposed by Teun A. Van Dijk (2000) as well. The data were collected from the tweets using #InternationalWomensDay. In addition, the descriptions of the data were displayed qualitatively. Overall, the results reveal that from the data analysis, the number game strategies became the most frequently used strategy in tweets using the #InternationalWomensDay and the fewest strategy used in this hashtag was pseudo-ignorance. In summary, every tweet made on Twitter using a particular hashtag tends to have a certain purpose.